Faktor - Faktor Yang Mempengaruhi Income Smoothing (Studi Empiris Perusahaan yang Terdaftar di BEI) - Salsabila Diva; Lailah Fujianti; Nelyumna (Jurnal Akuntansi, 2023)
Income smoothing is used to analyze earnings management patterns in order to maintain the consistency of company profts from period to period. This action was taken in response to the perception of fnancial statement users that proft is a metric for determining whether a company is good or bad. This study aims to determine the factors that inﬂuence income smoothing with empirical studies on manufacturing companies from 2019 to 2021. The number of sample companies used in this study was 231 samples after being selected using the purposive sampling method. Logistic regression analysis was tested using EViews 12 software as a research method. The results of this study explain that frm size has a negative eﬀect and frm age has a positive inﬂuence on income smoothing practices, while institutional ownership and proftability have no eﬀect on income smoothing practices. Keywords: company age, company size, earnings management, income smoothing, institutional ownership, proftability